Teaching The Syntactic Norms of The Russian Language – Formation of The Language Competence Among Students (Eurasian Research Bulletin, 2021)
Turning to the linguistic foundations of the structure of linguistic competence it should be recalled that language is a unity of all its levels (subsystems): phonetic, morphological, lexical, phraseological, and syntactic. This means that in the formed linguistic competence, all these subsystems of the language should be presented simultaneously and in interconnection. Hence follows the possibility of studying linguistic competence as a structural whole - the unity of all the named subsystems in the linguistic consciousness of a student.